My watercolor dialog 水彩故事 - Ng, Woon Lam (Ng Woon Lam, 2024)
My early art journey began with extensive involvement with watercolor painting. I was so fortunate to have the opportunity to learn about watercolor. It was economical as a starter kit for a less financially fortunate kid like me. I remember that I would save 10 cents per day from my 30 cents for pocket money for about 1 month when I was in my primary school so that I could afford to get an additional watercolor set for my casual painting exploration. Without it being so affordable, I would not have such a wonderful journey of art. That’s why I would tell all beginners to purchase materials that they can easily afford so that they could carry out the most fearless experiments and learn the most out of it. Along my journey of watercolor, there were so many unanticipated ups and downs that have truly enriched my life a s fine artist. While it has not been a smooth ride along the way, I still regard myself as a lucky one to have chosen watercolor as one of my major art media. My first mentor was my high school art teacher Mr. Chan Teck Kee who truly provided my with remarkable guidelines. His mentorship opened the gate of art to me. While I was trained as an engineer, my long-term goal was to be a fine artist and watermedia served the purpose when I could not set aside significant amount of space to store my experimental pieces. Watercolors are painted on paper and take up probably the least amount of space as all the finished pieces can be stacked up and stored in packs. In 1992 I had the opportunity to meet my long admired watercolor master Mr. Gog Sing Hooi. He was the late founding president of the Singapore Watercolour Society. While I only had a short period of mentorship of slightly more than a year from him before his unfortunate passing in 1994, his experience and great understanding in color application and calligraphical brushwork in watercolor have very significant influence of my learning of watercolor art and comprehension of painting language. Through master Gog’s recommendation, I continued to meet many great artists locally and internationally even after his passing. The 2 very active local art associations, the Singapore Watercolour Society (SWS) and the Singapore Art Society (SAS) have provided me with great exchange opportunities with their pools of experienced artists. Through one of the SWS’s invited talks, I was very fortunate to meet one of the American Watercolor Society master artist associate professor emeritus Chee Cheng-Khee. Coincidentally, professor Chee was a recipient of the Nanyang Achievement Award in 2008 presented by Nanyang Technological University (NTU). He is another influential mentor of mine who not only has guided me along my art career development, also regularly served as my recommender for my higher education in fine art and art academia career till today. There are small stories that I would love to share with all art enthusiasts together with my recent favorite watercolor artworks. I have this great opportunity to work with the Chinese Heritage Centre (CHC) at NTU to showcase my humble watercolors and the stories. I am very grateful to both both CHC’s invitation, especially associate professor Yow Chuen Hoe, director of CHC and Dr. Luo Biming, deputy director of CHC, who have provided various aspects of support for my watercolor solo exhibition at CHC exhibition gallery.